Financial Incentives in Vertical Diffusion: The Variable Effects of Obama's Race to the Top Initiative on State Policy Making. (June 2020) - Howell, William G.; Magazinnik, Asya
A substantial body of empirical work documents the influence of federal monies on state policy making. Less attention, however, has been paid to the conditioning effects of states' prior financial health. Nearly always, apportioned monies cover only a fraction of the costs of federal policy reforms. The capacity of states to deploy supplementary resources, therefore, may inform the willingness of states to comply with the federal government's policy objectives. Focusing on Barack Obama's Race to the Top (RttT) initiative, we present new evidence that state responses to federal initiatives that carry financial rewards systematically vary with the amount of resources already on hand. States that survived the Great Recession with their education budgets largely intact, we find, tended to implement more RttT reforms overall, and especially more reforms that required substantial up-front financial commitments. These patterns of policy adoptions can be meaningfully attributed to RttT, are not the result of either prior or ancillary policy trends, and speak to the general importance of accounting for what states already have, above and beyond what the federal government is willing to offer, when studying the financial incentives of vertical diffusion.